2020
DOI: 10.5334/aogh.2591
|View full text |Cite
|
Sign up to set email alerts
|

A Global View on Prevalence of Hypertension and Human Develop Index

Abstract: Background: The incidence of hypertension has been increasing in the past decade. Little is known regarding the relationship between hypertension and human development index (HDI). Objectives: The objective is to identify the relationship between the prevalence of hypertension and human development index (HDI). Methods: An ecological study was conducted. The data from World Health Organization reports and United Nations Development Programme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…42 A study conducted by Zeng et al to study the global prevalence of hypertension reported that it ranged from 13% to 41% worldwide. 43 It has been observed that hypertension is one of the prime factors in patients with atrial fibrillation (≈22%). 40,44 Study by Khurshid et al reported a prevalence of 2.35% baseline rhythm abnormality among the general population and a higher (4.84%) prevalence among population aged 65 to 73 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 A study conducted by Zeng et al to study the global prevalence of hypertension reported that it ranged from 13% to 41% worldwide. 43 It has been observed that hypertension is one of the prime factors in patients with atrial fibrillation (≈22%). 40,44 Study by Khurshid et al reported a prevalence of 2.35% baseline rhythm abnormality among the general population and a higher (4.84%) prevalence among population aged 65 to 73 years.…”
Section: Discussionmentioning
confidence: 99%
“… 42 A study conducted by Zeng et al to study the global prevalence of hypertension reported that it ranged from 13% to 41% worldwide. 43 …”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that hypertension is a severe public health challenge. Data have shown that the prevalence of hypertension ranged from 13 to 41% among 182 countries in the world, accounting for approximately 45% of the global cardiovascular morbidity and mortality ( Zeng et al, 2020 ). Exercise is one of the major non-pharmacological treatments for hypertension, and is broadly recommended by European and American hypertension guidelines ( Dimeo et al, 2012 ).…”
Section: Irisin and Cardiovascular Healthmentioning
confidence: 99%
“…Hypertension is one of the major causes of cardiovascularrelated morbidity and mortality in humans [1][2][3][4]. Epidemiological studies reported that excess dietary fructose (≥74 g/day) in the form of added sugar is associated with higher blood pressure (BP) values in adults who did not have a history of hypertension [5].…”
Section: Introductionmentioning
confidence: 99%